The SARM1 Toll/Interleukin-1 Receptor Domain Possesses Intrinsic NAD[+] Cleavage Activity that Promotes Pathological Axonal Degeneration. - Essuman, K.; Summers, D.W.; Sasaki, Y.; Mao, X.; DiAntonio, A.; Milbrandt, J. (Neuron, 2017)
Axonal degeneration is an early and prominent feature of many neurological disorders. SARM1 is the central executioner of the axonal degeneration pathway that culminates in depletion of axonal NAD+, yet the identity of the underlying NAD+-depleting enzyme(s) is unknown. Here, in a series of experiments using purified proteins from mammalian cells, bacteria, and a cell-free protein translation system, we show that the SARM1-TIR domain itself has intrinsic NADase activity-cleaving NAD+ into ADP-ribose (ADPR), cyclic ADPR, and nicotinamide, with nicotinamide serving as a feedback inhibitor of the enzyme. Using traumatic and vincristine-induced injury models in neurons, we demonstrate that the NADase activity of full-length SARM1 is required in axons to promote axonal NAD+ depletion and axonal degeneration after injury. Hence, the SARM1 enzyme represents a novel therapeutic target for axonopathies. Moreover, the widely utilized TIR domain is a protein motif that can possess enzymatic activity.